Placental Cyclophilin A Expression in Pregnancies Complicated with Hypertension - Elia Shazniza Shaaya (International Journal of Environmental Research and Public Health, 2022)
Introduction: Cyclophilin A was reported to be increased in the serum of mothers with preeclampsia, and is implicated in its pathogenesis. This study aimed to determine the expression of cyclophilin A in the placenta of mothers with and without hypertension, and to correlate its expression with maternal complications and adverse perinatal outcomes. Materials and Methods: This study consisted of a total of 70 cases (35 cases of mothers with hypertension, and 35 normotensive mothers as a control). Cyclophilin A immunohistochemistry was performed on a paraffin-embedded tissue section of placenta submitted at full thickness in order to evaluate the expression in fetal endothelial cells, cytotrophoblasts, syncytiotrophoblasts, maternal endothelial cells and decidual cells. The cyclophilin A expression was scored as weak, moderate or strong intensity. Results: The hypertensive group was more likely to have preterm deliveries (p < 0.0001), caesarean sections (p < 0.0001), and infants admitted to the intensive care unit (p < 0.001). Fifty-one percent of the fetal endothelial cells and cytotrophoblasts expressed cyclophilin A in the hypertensive group, compared to only 28.6% in the normotensive group. However, the difference was not statistically significant (p = 0.086). Conclusion: We found no significant difference in placental cyclophilin A expression between hypertensive and normotensive mothers. There was also no difference in expression in mothers with and without maternal complications and adverse perinatal outcomes.